Minimal and maximal solutions for two-point boundary-value problems - Myron K. Grammatikopoulos; Petio S. Kelevedjiev (Electronic Journal of Differential Equations, 2003)
In this article we consider a boundary-value problem for the equation ${f(t,x,x',x'')=0}$ with mixed boundary conditions. Assuming the existence of suitable barrier strips, and using the monotone iterative method, we obtain the minimal and maximal solutions.